Ring opening polymerization of lactide: kinetics and modeling - Metkar, Sangeeta; Sathe, Vivek; Rahman, Imran; Idage, Bhaskar; Idage, Susheela (Chemical Engineering Communications, 2019)
The ring opening polymerization (ROP) kinetics of L-lactide was studied in bulk at 150, 160, and 180 degrees C using stannous octoate [Sn(Oct)(2)] catalyst and 1-pyrene butanol co-catalyst. The effect of different parameters namely, time and co-catalyst to catalyst ratio was studied on the properties of polylactide. The experimental results showed high conversion of L-lactide. The kinetics of L-lactide ROP follows the co-ordination insertion mechanism. The experimental results obtained were studied to account for the reversible activation, propagation, termination, and validated by modeling using MATLAB. The model developed successfully predicts the monomer conversion and the kinetics of L-lactide ROP.
Keywords: 1-pyrene butanol; Average molecular weights; GPC; kinetics; L-Lactide; Modeling and simulation; Polymerization temperature; Proton NMR; ROP; Stannous octoate

Evaluation of biocompatibility of synthesized low molecular weight PLGA copolymers using zinc L-proline through green route for biomedical application - Giram, Prabhanjan S.; Garnaik, Baijayantimala (Polymers for Advanced Technologies, 2021)
Poly(lactide-co-glycolide) (PLGA) copolymers were synthesized by ring opening polymerization in presence of zinc proline and stannous octoate in bulk through green route and were designated as PLGA-1 and PLGA-2 respectively. These copolymers were characterized using NMR, SEC, DSC, X-ray and MALDI-TOF analysis. For the first time, the low molecular weight of PLGA (similar to 11,000 Da) was mainly targeted to explore acute oral toxicity in the presence of zinc L-proline and stannous octoate. The haemolysis and cell viability assay were carried out for in-vitro cytotoxicity assessment. Haemolysis assay of PLGA-2 was confirmed and haemolytic potential exceeded limit of American society of testing of material standard. The cell viability study using fibroblast cell lines (NIH3T3), exhibited statistically significant difference in results between PLGA-1 and PLGA-2. The acute toxicity study was performed in Balb/c mice for biomarker, hematological and histopathological analysis. No mortality was observed during the entire observation period, and no macroscopic change of the organs was observed in PLGA-1 treated group where PLGA-2 treated group showed sign of toxicity. The results obtained from in-vitro and in-vivo studies suggested that PLGA-2 was toxic whereas PLGA-1 was nontoxic in nature. Therefore, PLGA-1 can be regarded as biocompatible biomaterials for potential for drug delivery and biomedical application.
Keywords: OECD-420; poly (lactide-co-glycolide); ring opening polymerization; Stannous octoate; zinc L-Proline